Study of BC14N-bilayer graphene: Effects of atomic spacing and interatomic interaction between B and N atoms. (August 2021) - Abdullah, Nzar Rauf; Rashid, Hunar Omar; Gudmundsson, Vidar
Abstract: We study the effects of an attractive interaction between the boron (B) and the nitrogen (N) atoms doped in a bilayer graphene (BLG), BC14 N, on the electronic, the thermal and the optical properties for two different types of a doping process: First, both the B and the N atoms are doped in the same layer while the other layer is undoped. Second, the B and N atoms are doped in both layers. An attractive interaction between the B and N atoms does not influence the interlayer interaction in the first case, while it does in the second case. We find that the strong B-N attractive interaction in one layer induces metallic behavior due to the crossing of the valence band and the Fermi energy, while the strong attractive interaction between both layers induces a semiconductor property arising from the emergence a bandgap. We therefore confirm that the metallic-like BLG is not a good material for thermal devices because it has a low figure of merit, while we notice that the semiconductor-like BLG has a high Seebeck coefficient and figure of merit as well as a low thermal conductivity. The strong attractive interaction of the B-N atoms between the layers gives rise to a prominent peak to appear in dielectric function, the excitation and the absorption spectra in the low energy, visible range, while a very weak peak is seen in the case of a strong attractive interaction between the B and N doped in one layer. Last, the ferromagnetic and anti-ferromagnetic phases of the BN-codoped structures are also discussed. Controlling the B and N atomic configurations in the BLG may help to improve the material for use in both thermoelectric and optoelectronic devices. Highlights: Attractive interaction between BN dopant atoms decreases interlayer spacing of BLG. Attractive interaction induce a pronounced bandgap. Dielectric function, the excitation and the absorption spectra in the low energy, visible range, are enhanced. Thermoelectric efficiency is enhanced due to presence of attractive interaction.